The relation speed tolerances pulling strength and level of achievement in the 2000m (rowing) competition - Abdel-Latif , Iyad (Journal of Physical Education, 2011)
The research contains five chapters as follows : part1: research,s definition : the special tolerance of which is speed tolerance has a great importance in 2000m rowing activity by showing the player,s ability to continue of performing special loads at the same competition that work effectively to resist performance level to diclire . the research problem from the comes from the lack of interest in special tolerance in carring on the competition resuriements in the in creasing and organiled start point . part 2: the oritical studies in this parts the researcher shows the meaning of speed tolerance and putting strength and their effed in the achievement level . part 3: in this part ,the researcher shows that ,the research applied circulum is the description one purposed research speices of (10 player) and the use of tow tests for speed tolerance and pulling strength and the instruments used along with static means . part 4: the part shows the results manifestation , its analysis and its discussion in columns . part 5: the researcher points out conclesions and suggestion related to the research .